Registration of 'Scorpio' hard red winter wheat. Issue 1 (30th October 2020) - Carter, A.H.; Balow, K.A.; Shelton, G.B.; Burke, A.B.; Hagemeyer, K.E.; Stowe, A.; Worapong, J.; Higginbotham, R.W.; Chen, X.M.; Engle, D.A.; Murray, T.D.; Morris, C.F.
Abstract: Recent changes in the environment and crop management practices of the Pacific Northwest region of the United States have challenged the development of successful hard red winter (HRW) wheat ( Triticum aestivum L.) cultivars for the >500‐mm annual precipitation zones of the eastern part of the state of Washington. The use of N fertilizer and an increase in no‐till production practices have led to decreases in soil pH that can be toxic to wheat, especially in soils derived from previously forested land. The objective of this research was to develop a HRW wheat cultivar that combined tolerance to low‐pH soils with other important traits such as high yield, high grain volume weight, high grain protein concentration, acceptable end‐use quality, winterhardiness, and stripe rust resistance. 'Scorpio' (Reg. no. CV‐1169, PI 693629) HRW wheat was developed and released in March 2019 by the Agricultural Research Center of Washington State University. Scorpio was tested under the experimental designations HRW11064‐1‐DH‐1‐4 and WA8268. Scorpio is a semi‐dwarf cultivar adapted to the high‐rainfall wheat production regions of Washington. Scorpio is tolerant to low‐pH soils, has high‐temperature adult‐plant resistance to stripe rust, and has a midseason heading date, high grain volume weight, high grain protein concentration, and high grain yield. Scorpio has end‐use quality properties comparable to those of 'LCS Jet', 'Keldin', and 'Whetstone', which are acceptable for both domestic and export markets. Core Ideas: Development of hard red winter wheat cultivars for the state of Washington. Scorpio hard red winter wheat is tolerant of low‐pH soils with high concentrations of Al. Scorpio has adult‐plant resistance to stripe rust.